2018
DOI: 10.1007/s10071-018-1200-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of experience and of dots’ density and duration on the detection of coherent motion in dogs

Abstract: Knowledge about the mechanisms underlying canine vision is far from being exhaustive, especially that concerning post-retinal elaboration. One aspect that has received little attention is motion perception, and in spite of the common belief that dogs are extremely apt at detecting moving stimuli, there is no scientific support for such an assumption. In fact, we recently showed that dogs have higher thresholds than humans for coherent motion detection (Kanizsar et al. in Sci Rep UK 7:11259, 2017). This term re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…The lower this proportion of coherently moving dots the harder is the detection of coherent motion. The lowest proportion of coherently moving dots for which dogs were capable to detect coherent motion was 0.29, a lot higher than the threshold reported for adult humans of 0.05 9,10 . Thus, coherent motion detection seems to be more efficient in humans (and other mammals including macaques, cats, and seals [11][12][13] ) than in dogs.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…The lower this proportion of coherently moving dots the harder is the detection of coherent motion. The lowest proportion of coherently moving dots for which dogs were capable to detect coherent motion was 0.29, a lot higher than the threshold reported for adult humans of 0.05 9,10 . Thus, coherent motion detection seems to be more efficient in humans (and other mammals including macaques, cats, and seals [11][12][13] ) than in dogs.…”
contrasting
confidence: 57%
“…In Experiment 2, we fitted two models. In LMM 02, we included the predictor variables throw number (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and the Frisbee movement condition (rewind, forward). In LMM 03, we included the predictor variables interest period number (within condition; 1-3) and the Frisbee movement condition (rewind, forward).…”
Section: Subjectsmentioning
confidence: 99%
“…In adopting this approach, three non‐illusion studies have also evaluated canine perceptual processing preferences (albeit, for some, indirectly). Two studies have evaluated global‐local precedence using a Navon’s task (Mongillo et al, 2016; Pitteri, Mongillo, Carnier, & Marinelli, 2014), while another assessed motion perception (Kanizsár et al, 2018). The two studies that specifically evaluated global‐local precedence in dogs suggests dogs may process stimuli globally; however, these two studies used the same sample of subjects, and while a global processing preference in dogs was identified, this trend was not significant (Mongillo et al, 2016; Pitteri et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The two studies that specifically evaluated global‐local precedence in dogs suggests dogs may process stimuli globally; however, these two studies used the same sample of subjects, and while a global processing preference in dogs was identified, this trend was not significant (Mongillo et al, 2016; Pitteri et al, 2014). In the study of motion perception, it was reported that dogs locally integrate elements (Kanizsár et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation